2022-RA-1257-ESGO MILACC Study: Is the manipulation with LN containing undetected micrometastases the underlying cause of higher rate of local recurrences in the LACC trial?. (20th October 2022) - Cibula, David; Nitecki, Roni; Dundr, Pavel; Nemejcova, Kristyna; Ribeiro, Reitan; Vieira Gomes, Mariano Tamura; Schmidt, Ronaldo Luis; Bedoya, Lucio; Ortiz, David Isla; Pareja, Rene; Rendón Pereira, Gabriel Jaime; Blanco, Aldo López; et al.
Abstract : Introduction/Background: Etiology of inferior oncologic outcomes in minimally invasive surgery (MIS) in early cervical cancer remains unknown. Manipulation of lymph nodes (LN) with low volume disease could explain the discrepancy in survival in the LACC trial. We reviewed all pelvic lymph nodes by pathological ultrastaging for the presence of micrometastases in node negative (H&E) patients who recurred in the LACC trial. Methodology: Eligible patients for MILACC study were patients previously randomized to the LACC trial, had negative LNs, and recurred to any site within the abdomen and pelvis. Patients without recurrence, without available LN tissue, or with distant recurrence were excluded. Paraffin tissue blocks and slides from all LN removed by lymphadenectomy during primary surgery were re-analyzed utilizing standard ultrastaging protocol (all analyzed by central pathological center), aiming at the detection of isolated tumor cells (clusters up to 0.2 mm in diameter or <200 cells) and micrometastases (>0.2 and ≤2 mm). Results: A total of 20 patients were included. Median age of the cohort was 43 (range: 30–68). Most patients had squamous cell carcinoma (70%), were randomized to MIS arm of LACC trial (85%), had stage 1B1 (95%), did not receive any adjuvant treatment post-operatively (75%), and had a single recurrence site (55%), most commonly at vaginal cuff and pelvis (both 45%). The median number of lymph nodes analyzed per patient was 19 (range: 4–32) for a total of 412 LN. A total of 621 series and 1242 slides were reviewed centrally by the ultrastaging protocol. No metastatic disease of any size was found in any LN. Conclusion: There was no LN small-volume metastases among patients with initial negative LN who recurred in the LACC trial. The hypothesis that manipulation of LN with occult low volume disease as an explanation for the worse oncologic outcomes is not supported by our study.